Strategies and Roles of Mosque Youth in Reviving Ramadhan Activities: A Fiqih Maslahah Perspective in Kismoyoso Village - Chafia Tawakalluna Anidhita; Salma Nabila; Qodim Ma’shum (Smart: Journal of Global Islamic Studies and Social Science, 2026)
The digital disruption profoundly challenges contemporary mosques to transform from rigid ritual spaces into inclusive social epicenters. This qualitative field research comprehensively evaluates the social engineering strategies of mosque youth in Kismoyoso Village using the Fiqih Maslahah epistemological framework, specifically Asy-Syatibi’s Dhawabith al-Mashlahah. Findings reveal that youth transitioned into strategic managers by integrating ritual piety with substantive economic initiatives, such as inclusive digital propagation and the Ramadhan Fest. Furthermore, they successfully navigated intergenerational authority conflicts and mitigated juvenile delinquency through cultural negotiation and the application of Sadd ad-Dzari'ah. These adaptive strategies are legally validated as Maslahah Mursalah. Digital da'wa fulfills Hifzh ad-Din at the Hajiyyat level, while financial empowerment and security interventions firmly secure Hifzh an-Nafs and Hifzh al-Mal at the absolute Dharuriyyat level. Ultimately, this research establishes a transformative and progressive model for global mosque governance and community resilience to combat the moral degradation of modern Muslim youth populations.